Citra Ibu Dan Perlawanan Dalam Lirik Lagu Rusia Dan Palestina: Pendekatan Representasi Stuart Hall Dalam Kajian Sastra Bandingan - Arifin, Muhamad; Hisnullah, Muhammad Wildani; Azzuhri, Ibnu Shihab; Wulandari, Wulandari (Program Studi Bahasa dan Sastra Arab Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study aims to analyze and compare the representation of homeland and resistance in two songs from different cultures: “Mother” from Russia and “We Will Not Go Down” from Palestine. Songs are regarded as a form of oral literature rich in symbolic, ideological, and emotional meaning. Using Stuart Hall’s theory of representation and content analysis methods, this study examines how the image of the “mother” as a symbol of the homeland and resistance to oppression is constructed in the lyrics of both songs. The results show that the Russian song emphasizes emotional nationalism through metaphors of nature and motherhood, while the Palestinian song emphasizes a narrative of struggle using diction of resistance and symbols of destroyed homes and places of worship. These stylistic differences demonstrate that representation in song is highly influenced by each culture’s historical, political, and social context. This study also reinforces Hall’s theory that meaning is constructed through cultural processes, and expands the scope of comparative literature studies in cross-cultural musical contexts. These findings are essential in understanding that musical literature can serve as a medium for expressing identity and resistance across geographical and ideological boundaries